Activatable cell–biomaterial interfacing with photo-caged peptides. Issue 4 (16th November 2018) - Lin, Yiyang; Mazo, Manuel M.; Skaalure, Stacey C.; Thomas, Michael R.; Schultz, Simon R.; Stevens, Molly M.
Abstract : We report an effective strategy to design activatable cell–material interfacing systems enabling photo-modulated cellular entry of cargoes and cell adhesion towards surfaces. Abstract : Spatio-temporally tailoring cell–material interactions is essential for developing smart delivery systems and intelligent biointerfaces. Here we report new photo-activatable cell–material interfacing systems that trigger cellular uptake of various cargoes and cell adhesion towards surfaces. To achieve this, we designed a novel photo-caged peptide which undergoes a structural transition from an antifouling ligand to a cell-penetrating peptide upon photo-irradiation. When the peptide is conjugated to ligands of interest, we demonstrate the photo-activated cellular uptake of a wide range of cargoes, including small fluorophores, proteins, inorganic ( e.g., quantum dots and gold nanostars) and organic nanomaterials ( e.g., polymeric particles), and liposomes. Using this system, we can remotely regulate drug administration into cancer cells by functionalizing camptothecin-loaded polymeric nanoparticles with our synthetic peptide ligands. Furthermore, we show light-controlled cell adhesion on a peptide-modified surface and 3D spatiotemporal control over cellular uptake of nanoparticles using two-photon excitation. We anticipate that the innovative approach proposed in this work will help to establish new stimuli-responsive delivery systems and biomaterials.